(untitled) (Medico Legal Update, 2019)
Background/Objectives: The purpose of this study was to investigate the moderating effect of growth mindset on the mediating effect of stress on relationship between school violence victimization and school adaptation. Method/Statistical Analysis: The subjects of this study were 1,250 students living in H and S city of Chungnam-do, Korea. The collected data are analyzed using correlation analysis, frequency analysis, and moderating mediation effect. Findings: First, the correlation analysis showed a positive correlation between school violence victimization and stress, growth mindset and school adaptation. And, the school violence victimization was negatively correlated with a growth mindset and school adaptation, and stress was negatively correlated with a growth mindset and school adaptation. Second, the stress mediated the relationship between school violence victimization experiences and school adaptation. Third, growth mindset moderated the relationship between stress and school adaptation. Fourth, growth mindset moderated the mediating relationship of stress between school violence victimization and school adaptation. Improvements/Applications: Finally, based on the results of this study, it was suggested that the program to improve their growth mindset should be developed to increase school adaptation. In addition, we discussed regional comparisons through nationwide sampling, research on various age groups, and directions for research targeting only vulnerable groups.